2023
DOI: 10.1021/acs.jpca.3c02879
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Molecular Origin of g-Tensor Heterogeneity and Strain in Nitroxide Radicals in Water: Electron Paramagnetic Resonance Experiment versus Theory

Van Anh Tran,
Markus Teucher,
Laura Galazzo
et al.

Abstract: Nitroxides are common EPR sensors of microenvironmental properties such as polarity, numbers of H-bonds, pH, and so forth. Their solvation in an aqueous environment is facilitated by their high propensity to form H-bonds with the surrounding water molecules. Their g- and A-tensor elements are key parameters to extracting the properties of their microenvironment. In particular, the g xx value of nitroxides is rich in information. It is known to be characterized by discrete values representing nitroxide popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…The correlation diagrams presented above signify the robustness of V N in representing the HFCCs of nitroxide radicals. It is worth mentioning that factors such as solvent polarity, noncovalent interactions, temperature, pH, and physical state of the sample can influence the HFCC values, which are not considered in the present study. Nevertheless, our study demonstrated the usefulness of V N values to capture subtle changes associated with the steric and electronic nature of the substituents in nitroxide radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation diagrams presented above signify the robustness of V N in representing the HFCCs of nitroxide radicals. It is worth mentioning that factors such as solvent polarity, noncovalent interactions, temperature, pH, and physical state of the sample can influence the HFCC values, which are not considered in the present study. Nevertheless, our study demonstrated the usefulness of V N values to capture subtle changes associated with the steric and electronic nature of the substituents in nitroxide radicals.…”
Section: Resultsmentioning
confidence: 99%
“…While EC-RISM already yielded improved NMR shift results compared to PCM calculations on optimized structures, 27 its performance advantage was particularly evident in the context of calculating isotropic hyperfine coupling constants for electron paramagnetic resonance (EPR) spectroscopy, as demonstrated recently. 34,35 In a similar spirit as in the present work, we worked out the accuracy limit for such calculations on the basis of AIMD-generated ensembles of a spin probe in water. By comparing to fully explicit solvation with a quantum-mechanical/molecular-mechanical (QM/MM) approach, we showed that EC-RISM as a hybrid solvation model is capable of replacing the short-range explicit solvation effects, unlike PCM.…”
Section: Introductionmentioning
confidence: 99%